Processo decisório e inovação em serviços: um estudo a partir da trajetória de uma instituição hospitalar. - Vianna, Rodrigo de Souza (Universidade do Vale do Rio dos Sinos, 2015)
Proper coordination between decision-making and innovation in services can lead to success or failure of a company or institution. Innovation in services is also a result of a decision-making process, and this must be well managed in order to cover the possible consequences of this process, mainly to avoid any bias. The consideration of decision-making and innovation in services in hospitals is also justified because this theme is current. The hospital administration is a result of the system that has expanded, and the hospital is seen as a modern company. Competitive advantage in health can be achieved through differentiation strategies related to many factors causing costs (hospital and operational structure, culture of the organization, etc.) that need to be administered (Porter and Teisberg, 2007; Klock, 2009; Neves, 2009). The study sought to demonstrate how is the decision-making process for innovation in services in a hospital,whichrecently implemented new services and soon it will expand its entire physical structure (including new technologies and services). The study also covered a trajectory in order to demonstrate if the new services may have aided the recent results of the institution. In developing this work, surveys were conducted in doctrines, websites, articles, and data collection through documentation provided by the institution and interviews with some decision makers of the institution. As a general aim, the study wanted to identify the functioning of the decision-making process on innovation in services in a hospital setting, and check how these innovations impact the results of the institution. As for the specific objectives of this study they were to identify how the decision-making process works, which innovations in services have been implemented recently, and what were your goals, beyond of understanding the relationship between decision-making and innovation in services in the context of the study. Analyzing the data collected, we sought to understand whether the decisions taken on the new services actually benefited the performance of the institution. The main results suggest that there is a relationship, although not significant, between investments in new services and the results of the institution. Thus, the expansion of physical infrastructure, which will also be accompanied by new investments in technologies and services, suggests a positive conclusion as to the decision made.
Keywords: Processo decisório; Inovação em serviços; Serviços em saúde; Decision-making process; Innovation in services; Health services; ACCNPQ::Ciências Sociais Aplicadas::Administração